Optimization of functionally gradient materials in valve design under cyclic thermal and mechanical loading - Maciejewski, Grzegorz; Mróz, Zenon (Computer Assisted Methods in Engineering and Science, 2017)
The robust and simple optimization method of functionally graded material (FGM) for combined cyclic thermal and mechanical loading with application to valve design is proposed. The optimization procedure starts from the homogeneous ceramic material distribution and after thermomechanical analysis of the whole process, the new distribution of material is determined by reducing concentration of the ceramic phase at places of high tensile stresses and by increasing ceramic contents at places of high effective stresses. The optimal distribution of ceramic phase is found through iterations. We have shown the numerical example of the proposed method for optimization of a composite exhaust valve of combustion engine. The example illustrates the optimal density distribution of ceramic phase of Al2O3 within NiAl matrix. In the design study we have used the transient analysis of stress and temperature fields. The proposed method shares merits of standard optimization and topology optimization, it allows for creating one phase of material inside the other. It can be especially useful to problems of structural elements subjected to thermomechanical loading histories.